Fluorescent probe for the imaging of superoxide and peroxynitrite during drug-induced liver injury. Issue 11 (1st February 2021) - Wu, Luling; Liu, Jihong; Tian, Xue; Groleau, Robin R.; Bull, Steven D.; Li, Ping; Tang, Bo; James, Tony D.
Abstract : Drug-induced liver injury (DILI) is an important cause of potentially fatal liver disease. Abstract : Drug-induced liver injury (DILI) is an important cause of potentially fatal liver disease. Herein, we report the development of a molecular probe (LW-OTf ) for the detection and imaging of two biomarkers involved in DILI. Initially, primary reactive oxygen species (ROS) superoxide (O2 ˙ − ) selectively activates a near-infrared fluorescence (NIRF) output by generating fluorophore LW-OH . The CC linker of this hemicyanine fluorophore is subsequently oxidized by reactive nitrogen species (RNS) peroxynitrite (ONOO − ), resulting in cleavage to release xanthene derivative LW-XTD, detected using two-photon excitation fluorescence (TPEF). An alternative fluorescence pathway can occur through cleavage of LW-OTf by ONOO − to non-fluorescent LW-XTD-OTf, which can react further with the second analyte O2 ˙ − to produce the same LW-XTD fluorescent species. By combining NIRF and TPEF, LW-OTf is capable of differential and simultaneous detection of ROS and RNS in DILI using two optically orthogonal channels. Probe LW-OTf could be used to detect O2 ˙ − or O2 ˙ − and ONOO − in lysosomes stimulated by 2-methoxyestradiol (2-ME) or 2-ME and SIN-1 respectively. In addition, we were able to monitor the chemoprotective effects of tert -butylhydroxyanisole (BHA) against acetaminophen (APAP) toxicity in living HL-7702 cells. More importantly, TPEF and NIRF imaging confirmed an increase in levels of both O2 ˙ − and ONOO − in mouse livers during APAP-induced DILI (confirmed by hematoxylin and eosin (H&E) staining).